Susceptibility Zoning of Soil Movement in Tawangmangu District, Karanganyar Regency with Bivariate Statistic Method - Weight of Evidence - Dwika Rizki Wirawan; Agung Setianto; Esti Handini (Geological Engineering Department Universitas Gadjah Mada, 2022)
Tawangmangu district which is located in Karanganyar Regency, Central Java is a crowded area which is susceptible to disaster. Therefore, susceptibility zoning analysis is needed to support the planning and development of the area. The method used is bivariate statistics - weight of evidence which has never been implemented in its location. There are two types of data, data of potential and soil movement case (divided into train data as 61 points and test data as 40 points); and parameter data of soil movement causes. Parameter data of soil movement is processed to be a WoE (Weight of Evidence) parameter map through the use of train data to know the weight. Later on, it will be validated based on the AUC value. If it’s > 0,60, then the process will proceed. Parameter which has AUC value > 0,60 is type of lithology, slope, hill, elevation, slope direction, distance from the fault, and index of vegetation density. All of those parameters are attached and being final validated by test data. Further, the zonation consists of four; zone of very low soil movement susceptibility, low, medium, and high. The area of the very low soil movement susceptibility zone is 19,68%. Zone of low susceptibility is mostly 24,57%. Zone of medium susceptibility is 25,88%. Meanwhile, the zone of high susceptibility is 29,86%. The result of final validation shows that AUC value from the zoning model made belongs to a good category, which is 0,757.